From Good to Bad: The Opposing Effects of PTHrP on Tumor Growth, Dormancy, and Metastasis Throughout Cancer Progression - Edwards, Courtney M.; Johnson, Rachelle W. (Frontiers in Oncology, 2021)
Parathyroid hormone related protein (PTHrP) is a multifaceted protein with several biologically active domains that regulate its many roles in normal physiology and human disease. PTHrP causes humoral hypercalcemia of malignancy (HHM) through its endocrine actions and tumor-induced bone destruction through its paracrine actions. PTHrP has more recently been investigated as regulator of tumor dormancy owing to its roles in regulating tumor cell proliferation, apoptosis, and survival through autocrine / paracrine and intracrine signaling. Tumor expression of PTHrP in late stages of cancer progression has been shown to promote distant metastasis formation, especially in bone by promoting tumor-induced osteolysis and exit from dormancy. In contrast, PTHrP may protect against further tumor progression and improve patient survival in early disease stages. This review highlights current knowledge from preclinical and clinical studies examining the role of PTHrP in promoting tumor progression as well as skeletal and soft tissue metastasis, especially with regards to the protein as a regulator of tumor dormancy. The discussion will also provide perspectives on PTHrP as a prognostic factor and therapeutic target to inhibit tumor progression, prevent tumor recurrence, and improve patient survival.